Peran Efikasi Diri Sebagai Mediasi Pengaruh Literasi Digital Terhadap Keputusan Berwirausaha Program Mahasiswa Wirausaha (PMW) UNJ Angkatan 2023 - Alicia Florentina; Henry Eryanto; Maulana Amrul Adha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the effect of digital literacy on entrepreneurial decisions among students of Universitas Negeri Jakarta participating in the 2023 Student Entrepreneurial Program (PMW), with self-efficacy as a mediating variable. A quantitative approach was employed using a survey method. A total of 136 respondents were selected from 206 students in the TOP 50 PMW business teams through purposive sampling. Data were collected using a questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results show; (1) that digital literacy has a positive and significant effect on self-efficacy; (2) digital literacy has a positive and significant effect on entrepreneurial decisions; (3) self-efficacy has a positive and significant effect on entrepreneurial decisions; (4) and digital literacy indirectly affects entrepreneurial decisions through self-efficacy. These findings highlight the crucial role of self-efficacy in strengthening the influence of digital literacy on entrepreneurial decisions. Therefore, it is essential for higher education institutions to foster students' digital literacy and confidence to support entrepreneurial development in the digital era.